A novel hybrid SWARA and VIKOR methodology for supplier selection in an agile environment - Alimardani, Maryam; Hashemkhani Zolfani, Sarfaraz; Aghdaie, Mohammad Hasan; Tamošaitienė, Jolanta (Technological and Economic Development of Economy, 2013)
The concept of the agile supply chain has been taken into account as means of achieving a high competitive edge in rapidly changing business environments. Supply partner selection is one of the most appealing issues for agile supply chain management, which have recently been studied by academicians and practitioners. Due to a large number of factors to be considered, supplier selection process is a difficult task for every company. Therefore, supplier selection process can be viewed as a multiple attribute decision-making (MADM) problem. In this paper, a novel hybrid MADM method is proposed for agile supplier selection based on four criteria including performance, cost, flexibility and technology. Two MADM methods, including step-wise weight assessment ratio analysis (SWARA) and Vlse Kriterijumska Optimizacija I Kompromisno Resenje (VIKOR) are applied in decision-making process. More precisely, SWARA is used for determining the importance of each criterion and calculating their weights and VIKOR is applied for evaluating alternatives as well as ranking supplier alternatives from the best to the worst. More precisely, the first phase of the proposed methodology, step-wise weight assessment ratio analysis (SWARA), is useful for determining the importance of each criterion and calculating the weight of each criterion, and the second phase with Vlse Kriterijumska Optimizacija I Kompromisno Resenje (VIKOR) is useful for evaluating alternatives as well as ranking supplier alternatives from the best to the worst. Finally, a real case-study is presented to demonstrate the applicability of the proposed methodology. As a result, the model can help managers to evaluate and select the best supplier regarding own company strategies, resources, policies and etc. for their organization.